Phytochemical, cytotoxic and acetylcholinesterase inhibition in Kacip Fatimah (Labisia pumila (blume) fern.-vill.) penarahan (Horsfieldia superba (HK. F. & TH.) warb) and paku layar (Odontosoria chinensis (L.) J. SM.) extracts - Naji Al-Mekhlafi, Nabil Ali (2011)
In the present study, three Malaysian plants, specifically Labisia pumila(Myrsinaceae), Horsfieldia superba (Myristicaceae) and Odontosoria chinensis(Dennstaedtiaceae) were investigated for their chemical constituents. The plant materials were extracted and purified by chromatographic techniques. In total, forty two compounds were isolated, six of which are new compounds. These compounds can be classified into eight types based on their skeletons: alkyl phenols, dimeric 1,4-benzoquinone derivatives, terpenes, phenols derivatives, flavonoids, fatty acid,dihydrochalcone and α,β-unsaturated lactones. The structures of these compounds were fully characterized by various physical (melting point, optical rotation) and spectral (UV, IR, ID and 2D NMR, EIMS, and ESIMS) techniques. Phytochemical investigation on the leaves of Labisia pumila (Kacip Fatimah) (Myrsinaceae), an important medicinal herb in Malaysia, has led to the isolation of three new compounds, characterized as 1-acetoxy-4-hydroxy-2-methoxy-6-(pentadec-10Z-enyl)benzene (33), labisiaquinone A (34) and abisiaquinone B (35). Along with these, sixteen known compounds including 1-acetoxy-4-hydroxy-2-methoxy-6-pentadecylbenzene (36), 1,3-dihydroxy-5-(pentadec-10Z-enyl)benzene (37), 1,3-dihydroxy-5-pentadecylbenzene (38), (9Z,12Z)-octadeca-9,12-dienoic acid (39), stigmasterol 3-O-β-glycopyranoside (40), (-)-loliolide (41), stigmasterol (42), 4-hydroxyphenylethylamine (43), 3,4,5-trihydroxybenzoic acid (44), 3,4-dihydroxybenzoic acid (27), (+)-catechin (45), (-)-epicatechin (46), kaempferol 3-O-α-rhamnopyranosyl-7-O-β-glycopyranoside (47), kaempferol 3-O-α-rhamnopyranoside (48), kaempferol 4′-O-β-glycopyranoside (49), quercetin 3-O-α-rhamnopyranoside (50) were also isolated and identified. All the isolated compounds were reported for the first time from Labisia pumila species. Phytochemical investigation of methanol extract of the bark of Horsfieldia superba led to the isolation of the nineteen compounds (27, 51-68). Among these, three compounds (51-53) were found to be new, where compounds 52 and 53 were previously reported as a synthetic α,β-lactone. These compounds were characterized as (-)-3,4′,7-trihydroxy-3′-methoxyflavan (51), (-)-5,6-dihydro-6-undecyl-2H-pyran-2-one (52), (-)-5,6-dihydro-6-tridecyl-2H-pyran-2-one (53). Sixteen other known compounds were identified as (-)-viridiflorol (54), hexacosanoic acid (55), β-sitosterol (56), methyl 2,4-dihydroxy-6-methylbenzoate (methyl orsellinate) (57), methyl 2,4-dihydroxy-3,6-dimethylbenzoate (58), (-)-4′-hydroxy-7-methoxyflavan (59), (-)-4′,7-dihydroxyflavan (60), (-)-4′,7-dihydroxy-3′-methoxyflavan (61), (+)- 3,4′,7-trihydroxyflavan (62), (-)-catechin (63), (-)-epicatechin (46), (-)-7-hydroxy-3′,4′-methylenedioxyflavan (64), 2′,3,4-trihydroxy-4′-methoxydihydrochalcone (65),3′,4′,7-trihydroxyflavone (66), (+)-4′-hydroxy-7-methoxyflavanone (liquiritigenin 7- methyl ether) (67), hexadecanoic acid (palmitic acid) (68). Four pure aromatic compounds were isolated from the leaves of Odontosoria chinensis (Dennstaedtiaceae), which were characterized as 3,4-dihydroxybenzoic acid (27)3,4-dihydroxybenzaldehyde (28), 4-hydroxy-,5-dimethoxybenzoic acid (70) and 4-hydroxy-3-methoxybenzoic acid (71).The cytotoxic and acetylcholinesterase (AChE) inhibitory activities of crude fractions and the isolated compounds from the L. pumila, H. superba and O. chinensis were studied. Compounds, including 1-acetoxy-4-hydroxy-2-methoxy-6-(pentadec-10Z-enyl)benzene (33) and 1-acetoxy-4-hydroxy-2-methoxy-6-pentadecylbenzene (36) showed strong activity against three cancer cell lines: MCF-7 (breast), HCT-116 (colon) and PC-3 (prostate) with IC50 values 0.5-0.7 μM, whereas compounds (-)-5,6-dihydro-6-undecyl-2H-pyran-2-one (52) and (-)-5,6-dihydro-6-tridecyl-2H-pyran-2-one (53) showed moderate growth inhibition potency against the tested cell lines. The chloroform and ethyl acetate fractions of H. superba were found to exhibit moderate AChE inhibitory activity (IC50 72 and 60 μg/ml), whereas fractions from L. pumila and O. chinensis and hexane fraction of H. superba showed poor inhibition (IC50 >100).